(3GdJhSW hGdaJM Hjf GdQhVI hGdTQMs - (3TgGH GdOjf CMeO Hf MeOGf GdCPQYis; (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s
(3ChdgG (B:s
(3bGd GdQGgf eefhY s
(3BNQgG (B:s
(3EPG dGeYfi dEQGOI GdeWGdHI GdeMOOI Yf GdbHV Je hced GdLRA GdNGeS HMeO Gddg JYGdi s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B103s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs